Use of ChatGPT to Enhance English Speaking Skills: Learners’ Perception in a Sri Lankan University - Pushpakumara, P.B.S.L. (University of Jaffna, 2025)
Innovations in technology have significantly transformed the educational landscape in recent years. ChatGPT is one such innovation that plays an evolving role in education. Studies have been conducted to examine the use of ChatGPT to enhance writing among English as second language (ESL) learners, yet research on the use of ChatGPT to develop speaking skills of the ESL learners remains limited. The present study, therefore, investigated the perception of undergraduates regarding the use of ChatGPT voice over generator to develop their speaking skills. ChatGPT voice over generator enables the learners to orally interact with the app in real time, and this app offers spontaneous personalized responses. Using non – probability convenience sampling techniques, forty-three (N-43) students from a state university in Sri Lanka were selected for the mixed-methods research. After the participants experienced the use of ChatGPT voice over generator in the classroom, they were asked to fill out a questionnaire which consisted of fourteen closed ended questions and three open-ended questions. Quantitative analysis of the closed ended questions and qualitative content analysis of the data received through the three open ended questions revealed that the majority of the participants had not used ChatGPT for learning purposes before, yet all of them believed that ChatGPT voice over generator app was very helpful to enhance their speaking skills. Similarly, 97.7% of the participants believed that ChatGPT is effective in helping them to develop their English-speaking skills. Further, 86% of the participants were confident that ChatGPT voice over generator has the potential to develop their speaking skills. Majority of students (74.5%) preferred to talk with ChatGPT voice over generator more than with their friends or the teacher because ChatGPT voice over generator does not laugh at their mistakes, and the app is accessible twenty-four hours a day and seven days a week. Therefore, vast majority of the participants (90.7%) were satisfied with the app. However, ChatGPT voice over generator is not without limitations. For instance, 60.5% of the participants found it difficult to understand the accent. Qualitative data too supported this view. However, difficulty in understanding the accent is a characteristic of the language learning process, yet exposure to the standard accent of ChatGPT voice over generator is beneficial to the learners. Repeated exposure to the standard accent may help learners understand and produce the target language more accurately and naturally over time. Poor internet facility was also identified as another significant challenge. Infrastructure in universities can be developed to integrate technology more effectively in language classrooms and other similar contexts. Future research needs to be conducted to empirically investigate the impact of ChatGPT voice over generator app to develop the oral proficiency of the ESL students using more rigorous research designs such as experimental or quasi-experimental designs. Also, it is important to explore the long-term effect of using ChatGPT voice over generator on the development of learner confidence to engage in conversations with humans. Such research may shed further insight into the effectiveness of integrating ChatGPT into the ESL classroom.
Keywords: ChatGPT voice over generator; Perception; English speaking skills